Evaluation of a community-based, family focused healthy weights initiative using the RE-AIM framework - Mary E. Jung; Jessica E. Bourne; Heather L. Gainforth (BMC, 2018)
Abstract Background Childhood overweight and obesity is a major public health concern. Community-based interventions have the potential to reach caregivers and children. However, the overall health impact of these programs is rarely comprehensively assessed. This study evaluated a physical activity and healthy eating family program (Healthy Together; HT) using the RE-AIM framework. Methods Ten sites implemented the 5-week program. Thirty-nine staff members and 277 program participants (126 caregivers [M age  = 35.6] and 151 children [M age  = 13]) participated in the evaluation. Each RE-AIM dimension was assessed independently using a mixed-methods approach. Sources of data included archival records, interviews and surveys. Effectiveness outcome variables were assessed at pre- and post-intervention and 6-month follow-up. Results Reach: HT participants were almost entirely recruited from existing programs within sites. Effectiveness: Caregivers' nutrition related efficacy beliefs increased following HT (ps < .03). Participation in HT was not associated with significant changes in physical activity or nutrition behaviour or perceived social support (ps > .05). Knowledge surrounding healthy diets and physical activity increased in children and caregivers (ps < .05). Adoption: Thirty-five percent of sites approached to implement HT expressed interest. The 10 sites selected recruited existing staff members to implement HT. Implementation: Program objectives were met 72.8% of the time and 71 adaptations were made. HT was finance- and time-dependent. Maintenance: Two sites fully implemented HT in the follow-up year and 5 sites incorporated aspects of HT into other programs. Conclusions Working alongside organizations that develop community programs to conduct comprehensive, arms-length evaluations can systematically highlight areas of success and challenges. Overall HT represents a feasible community-based intervention; however further support is required in order to ensure the program is effective at positively targeting the desired outcomes. As a result of this evaluation, modifications are currently being implemented to HT.